P91 Development And Implementation Of A Structured, Annual 'comprehensive Respiratory Assessment' For Individuals With Advanced Copd. (10th November 2014) - Toms, N; Greening, NJ; Free, R; Williams, JE; Evans, RA; Steiner, MC
Abstract : Introduction: Disease burden, polypharmacy, co-morbidities and complex social needs are significant in patients with advanced COPD and predict morbidity, mortality and health care utilisation. Our first aim was to develop a structured annual assessment for patients with advanced COPD: the 'Comprehensive Respiratory Assessment (CRA)' to systematically assess disease burden, co-morbidities and social care needs akin to the 'Comprehensive Geriatric Assessment'. The second aim was to use the CRA in an out-patient setting to inform an individualised care plan. We report our first year experience of implementing an Advanced COPD Clinic with an annual CRA. Methods: A multi-disciplinary team developed the Comprehensive Respiratory Assessment (CRA) for patients with advanced COPD which was defined as an FEV1 of <50% predicted with one of the following: MRC ≥ 4, Respiratory Failure, ≥2 hospital admissions with an acute exacerbation of COPD, current smoking history, and a low BMI or significant weight loss. A bespoke electronic patient record (the airways disease database [ADD]) was developed to support the CRA. The CRA was performed annually by an advanced COPD nurse and subsequently reviewed in an out-patient clinic by a respiratory physician supported by a multi-disciplinary team whereby an individualised care plan was agreed with the patient. Ethical approval was sought and written consent provided. Results: The Advanced COPD service and CRA was established in June 2013 in Leicester, UK. The CRA is categorised into four principal domains which are: (1) exercise and activity, (2) exacerbations, (3) co-morbidities and extra-pulmonary manifestations, and (4) prognostic indicators and end of life care needs. At one year 155 referrals have been made with 71 annual CRAs completed to date. The baseline data of the patient cohort are described in Table 1 . Conclusion: The innovation of an advanced COPD service, with a multi-disciplinary team, supported by an annual Comprehensive Respiratory Assessment and bespoke electronic patient record is feasible and allows systematic assessment, development of individualised treatment plans, and further characterisation of this cohort.